2023
DOI: 10.1093/chemse/bjad005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of human sweet taste receptor subunits T1R2 and T1R3 to activation by glucose enantiomers

Abstract: We have previously shown that L-glucose, the non-caloric enantiomer of D-glucose, activates the human sweet taste receptor T1R2/T1R3 transiently expressed in HEK293T cells. Here we show that D- and L-glucose can also activate T1R2 and T1R3 expressed without the counterpart monomer. Serine mutation to alanine in residue 147 in the binding site of T1R3 VFT domain, completely abolishes T1R3S147A activation by either L or D-glucose, while T1R2/T1R3S147A responds in the same way as T1R2 expressed without its counte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…2A). Dubovski et al showed that the T1R2 (NM_152232.4) is more sensitive to presence of D-glucose 10 . In order to understand whether these SNPs affect the sensitivity of activation by D 2 O, we compared the dose response curves of HEK293T cells, transfected with either the T1R2 (NM_152232.1) or the more sensitive version (NM_152232.4), along with T1R3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2A). Dubovski et al showed that the T1R2 (NM_152232.4) is more sensitive to presence of D-glucose 10 . In order to understand whether these SNPs affect the sensitivity of activation by D 2 O, we compared the dose response curves of HEK293T cells, transfected with either the T1R2 (NM_152232.1) or the more sensitive version (NM_152232.4), along with T1R3.…”
Section: Resultsmentioning
confidence: 99%
“…Varying concentrations of deuterium Oxide were tested among different transfections; T1R2(NM_152232.1)/T1R3(black), T1R3/T1R3(blue) or T1R2/T1R2(NM_152232.1, pink). (B) Dose-response curves of HEK293T cells transiently transfected with T1R2(NM_152232.1)/T1R3 (black); or T1R2(NM_152232.4)/T1R3 (grey); All data were normalized based on maximum response of the full sweet taste heterodimer receptor 10 T1R2/T1R3 to 0.96M glucose. All tested solutions were done in at least triplicate; each experiment (transfection) was repeated three to five times.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations